Rethinking End Rhymes with "Alef-e-Etlaq" from a Linguistic and Rhetorical Perspective in Ferdowsi's Shahnameh - Nasrin Ghorbani; Yadollah Shokri; Navid Firouzi (مطالعات زبانی و بلاغی)
Ferdowsi is very subtle and precise in the use of rhyme. One of the points that has received less attention in the subject of rhyme is the investigation of the rhetorical role of rhyme in different literary and linguistic fields. In Shahnameh, Ferdowsi has used "alef-e-etlaq" in some cases as an end rhyme, which most of the researchers have considered as extra (al-zaidi), used to add weight to the verse, and ignored its rhetorical value. In this research, an attempt has been made to take a closer look at this "alef-e-etlaq" from a linguistic and rhetorical point of view. Since the time of Shams Qays, due to Shams' negative view of this “alef-e-etlaq”, it has mostly been undermined. In this article, we have tried to change the views of the past about this alphabet and introduce it not as a gross weakness in the Shahnameh, but as a kind of stylistic feature in a certain period.